2018
DOI: 10.1093/ntr/nty231
|View full text |Cite
|
Sign up to set email alerts
|

Dual Users Compared to Smokers: Demographics, Dependence, and Biomarkers

Abstract: Introduction The availability of electronic cigarettes (e-cigarettes) has profoundly changed the tobacco product landscape. In the United States, almost 6 million adults use both combustible and e-cigarettes (ie, dual users). The goal of this study was to understand how smokers and dual users differ in terms of demographics, cigarette dependence, and exposure to carcinogens. Methods An observational cohort (smokers, n = 166, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 33 publications
7
38
0
Order By: Relevance
“…Of the 422 participants who were enrolled at baseline, 322 (76.3%) completed the year 1 assessment. Table 1 shows that the smokers and dual users who completed the year 1 assessment differed on multiple baseline variables including race, education, and cigarettes smoked per day, consistent with the findings published previously using the full sample 36 . With respect to attrition during the first year of this observational trial, among the dual users, women were more likely to complete the year 1 assessments than were men (87.8% vs. 74.3%, χ 2 = 7.34, p = .01) and year 1 completers were significantly older than were noncompleters (40.57 [SD = 13.82] vs. 32.51 [SD = 11.93], t = −4.18, p < .001).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Of the 422 participants who were enrolled at baseline, 322 (76.3%) completed the year 1 assessment. Table 1 shows that the smokers and dual users who completed the year 1 assessment differed on multiple baseline variables including race, education, and cigarettes smoked per day, consistent with the findings published previously using the full sample 36 . With respect to attrition during the first year of this observational trial, among the dual users, women were more likely to complete the year 1 assessments than were men (87.8% vs. 74.3%, χ 2 = 7.34, p = .01) and year 1 completers were significantly older than were noncompleters (40.57 [SD = 13.82] vs. 32.51 [SD = 11.93], t = −4.18, p < .001).…”
Section: Resultssupporting
confidence: 86%
“…See Table 2 for additional baseline e-cigarette use characteristics among dual users. 36 Product Use and Transitions Over 1 Year…”
Section: Resultsmentioning
confidence: 99%
“…Termed ‘dual use’, many individuals report concurrent use of electronic cigarettes (e‐cigarettes) and combustible cigarettes (cigarettes) . Dual use could attenuate harm by reducing use of cigarettes with partial substitution of nicotine from e‐cigarettes or increase harm by delaying quitting cigarettes and increasing cumulative exposure to tobacco toxicants . Recent data suggest that, for many, dual use is not a path towards cigarette quitting .…”
Section: Introductionmentioning
confidence: 99%
“…Dual use could attenuate harm by reducing use of cigarettes with partial substitution of nicotine from e‐cigarettes or increase harm by delaying quitting cigarettes and increasing cumulative exposure to tobacco toxicants . Recent data suggest that, for many, dual use is not a path towards cigarette quitting . For example, although most report using e‐cigarettes for smoking cessation , 88% of dual users have continued dual use (44.3%) or cigarette‐only use (43.5%) over 1 year in one study .…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies also suggest significant associations between cigarette QF self‐reports and biological measures among nondaily smokers, 24,25 although a study of Italian teens found poor sensitivity of self‐report relative to hair analysis 26 . Similar studies have indicated strong correlations between QF measures and biomarkers among adolescent vapers 27 and adult daily smokers who also used e‐cigarettes 28 …”
Section: Introductionmentioning
confidence: 98%